2020
DOI: 10.7759/cureus.7083
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerability of Ashwagandha Root Extract in the Elderly for Improvement of General Well-being and Sleep: A Prospective, Randomized, Double-blind, Placebo-controlled Study

Abstract: Background Ashwagandha is an excellent adaptogen that is being used since ancient times in Ayurvedic medicine. Traditionally, it is used for various ailments and general well-being, including the treatment of geriatric patients. Managing quality of life (QoL) remains a challenge for the elderly population, especially joint pain management, sleep, and general well-being. With a growing global elderly population, QoL management with efficient medication and supplementation is the major healthcare requirement. Ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 26 publications
0
39
0
1
Order By: Relevance
“…We included five trials with a total of 400 participants [45,[53][54][55][56]. Table 1 further describes the studies included.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…We included five trials with a total of 400 participants [45,[53][54][55][56]. Table 1 further describes the studies included.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Out of the five trials, one trial declared that their study was partially sponsored by the manufacturer [45]. All trials were conducted in India [45,[53][54][55][56]. Three of the trials recruited participants from outpatient clinics [54][55][56], one trial recruited through phone call [45], and one trial did not mention the method of recruitment [53].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…More research comparing sex differences is needed, considering that it seems the production of testosterone derivatives (e.g., DHEA) from withanolides may lead to important differences. In this sense, the positive benefits on the hormonal profile (DHEA-S and testosterone) in overweight men over 50 s [ 65 ], on the immediate and general memory, executive function, attention and speed of information processing in subjects aged 50 with mild cognitive impairment [ 73 ], and on the quality of life, mental alertness and quality of sleep in healthy men and women over 70 s [ 74 ], makes the Ashwagandha root extract a nutritional alternative to optimize physical condition, bone and muscle health while preventing loss of muscle mass and strength in elderly.…”
Section: Discussionmentioning
confidence: 99%
“…A similar trial performed by Langade et al confirmed that ashwagandha can be used as an anxiolytic as well as for treating insomnia and enhancing sleep quality compared to a placebo [73]. Kelgane et al studied whether an extract of ashwagandha could be used in the elderly for general health and sleep quality, with the outcomes, as measured with different scales, demonstrating that ashwagandha supplementation could be an effective alternative to counter issues associated with aging, including sleep quality and mental alertness [74]. Deshpande et al showed improved sleep quality in healthy patients suffering from nonrestorative sleep after treatment with a standardized extract of ashwagandha [75].…”
Section: Withania Somniferamentioning
confidence: 96%